Drone fiction, empathy gap and the reader: Mohsin Hamid's short story Terminator: Attack of the Drone (2011). Issue 3 (4th March 2023) - Liaqat, Qurratulaen
ABSTRACT: This article contends that the analysis of drone fiction from the perspective of Reader-Response Theory yields valuable insights into the configuration of this newly emerging genre and constitutes a neo Reader-Response theoretical paradigm. Drawing on insights from Reader-Response Theory and drone fiction critical approaches, this study delineates how Mohsin Hamid's short story Terminator: Attack of the Drone (2011) prompts readers to affectively engage in the process of reconstructing this text and empathise with the drone victims. By conducting a textual analysis of the narrative strategies and literary devices, this article demonstrates that how this narrative simultaneously exploits the notion of 'empathy gap', inherent in the drone fiction theory, and the propositions of Reader-Response theory related to 'gaps' to unpack the ongoing dehumanisation of certain races and communities in contemporary milieu. I contend that this short text evokes empathy of readers and encourages them to reconfigure the humanity of the drone victims. Hence, Hamid's drone fiction acts as an aesthetic conduit which invokes readers to become active participants in the process of deciphering the social, racial, political and humanitarian repercussions of unprecedented drone warfare and to recognise the socio-political epistemology of 'being human' under drone warfare.